Numerical Analysis of External Flow Heat Transfer Around Slightly-Curved Surfaces - Can, Omer F.; Celik, Nevin; Dagtekin, Ihsan (Springer Heidelberg, 2014)
In the present study, heat transfer around curved surfaces, such as slightly-convex and slightly-concave surfaces, is investigated numerically. The curvature ratio R varied by varying the ratio of the final apex-to-chord line distance to curvature-radius (r), where the final apex-to-chord line distance to be as 0.05, 0.1 and 0.2 m while the curvature-radius (r) keeps constant as 0.05 m (, 2 and 4). The results are parameterized by Reynolds number Re, ranged from 40,000 to 400,000. Air flow around a circular cylinder body is also simulated for verifications. The heat transfer results have graphically been presented in terms of local Nu numbers. New correlations of average Nu numbers are also derived for both slightly-convex and slightly-concave configurations. As a result, it was concluded that average and local Nusselt numbers decrease with increasing surface curvature ratio R for convex surfaces, whilst they increase for concave surfaces.
Keywords: Curved surface; External flow; Numerical analysis